Роль органов чувств в ориентации леща, синца, плотвы и густеры Киевского водохранилища - Абросимова, А.М. (Вестник зоологии, 1976)
In spring period the fishes under experiment from the Kiev reservoir was taken southward or northward of the place of catch. In the studied individuals the vision, sense of smell and lateral line were eliminated in various combinations. Reliability of difference between returns of control individuals and those under experiment made it possible to study the effect of eliminated sense organs on fish orientation in homing. It is established that orientation of fish is disturbed when vision and the lateral line are eliminated simultaneously. So, vision and the lateral line might be the leading receptors in homing of fish under conditions of the Kiev reservoir.